Chemically Laminated 2D Bis(terpyridine)metal Polymer Films: Formation Mechanism at the Liquid–Liquid Interface and Redox Rectification. Issue 44 (4th July 2022) - Komeda, Joe; Takada, Kenji; Maeda, Hiroaki; Fukui, Naoya; Tsuji, Takuya; Nishihara, Hiroshi
Abstract: Recent studies on molecular 2D materials with high tunability of structure and function have focused mostly on the discovery of new precursors. Here, we demonstrate a facile one‐pot synthesis of laminated 2D coordination polymer films comprising bis(terpyridine)iron and cobalt at a water/dichloromethane interface. Cross‐sectional elemental mapping unveiled the stratum‐like structure of the film and revealed that the second layer grows to the dichloromethane side below the first layer. Cyclic voltammetry clarified that the bottom layer mediates charge transfer between the top layer and the substrate in a narrow potential region of mixed‐valence states. Furthermore, the bilayer film sandwiched by electrodes in a dry condition shows stable rectification character, and the barrier voltage corresponds to the redox potential difference between the two layers. This study introduces a new strategy for polymer design to explore the materials science of molecular 2D materials. Abstract : Redox rectifiers : Heterolaminated 2D coordination polymer films were synthesized at a liquid‐liquid interface, and the mechanism of film growth was revealed. The bilayer films show unique redox behavior based on the electron transfer mediation in an electrolyte solution and stable rectification characteristics when the film is sandwiched by electrodes in a dry state.